Implementasi Thariqah Al Intiqaiyyah ( Metode Eklektik ) Pada Pembelajaran Bahasa Arab Di MTSN Kediri 1 - Ahmad Rifa’i (LP2M Institut Agama Islam Negeri (IAIN) Kediri, 2015)
The success of a learning process will not be separated from the method used, because the teaching method isÂ one factor an very important role in the learning process. A method very big role in learning and concerned withÂ students also who become the object of learning. The appropriateness of the teacher in choosing the methodÂ of learning is one of the factors success of a teacher. in Research Implementation Eclectic Method in TeachingÂ Arabic in MTsN Kediri 1 result is Learning Maharah al qiraâ€™ah in MTsN Kediri 1 method is used; Speech Method,Â Drill method, Thariqah samâ€™iyyah syafahiyyah, Thoriqoh qawaâ€™id wa al Tarjamah, question method, recitationÂ method. Maharah Kalam is the method used; Drill method, Role Playing method, Thoriqoh al Mubasyarah etc.Â In learning Tarkib/qawaâ€™id method used is; Speech method, Qiyasiyyah method, qowaid wa tarjamah method,Â recitation method. Learning Maharah Istima â€˜method is used; Speech Method, Samâ€™iyyah syafahiyyah Method,Â Drill Method etc. While the obstacles encountered is the background student of heterogeneous input ArabicÂ language skills and lack of time learning Arabic and the solution by holding Learning Book yellow (BKK), ReadÂ and Write Qurâ€™an (BTQ) and add homework.